Increasing Engagement in Kitten Fostering Programs: Lessons Learned From High Kitten Intake Zip Codes in Los Angeles County - McDonald, Shelby E.; Miller, Gregory S.; Fried, Tina Reddington; Olmedo, Debra; Matijczak, Angela (Frontiers in Veterinary Science, 2022)
The goal of the current study was to identify ways to increase awareness and engagement in kitten fostering programs (KFPs) among residents of areas with a high intake of kittens to animal shelters in Southern California. Specifically, we aimed to understand residents’: 1) awareness of KFPs and kitten overpopulation issues, 2) interest in fostering kittens with an animal welfare organization, 3) concerns about fostering, 4) perceived ability to meet common KFP requirements, and 5) perceptions of potential KFP marketing/messaging and communication methods. Participants included 283, predominantly Latino/a/x adults aged 18 years or older who resided in Los Angeles County and who lived in one of 12 zip codes with a high rate of kitten shelter intake. Survey results indicated that more than one quarter of participants had engaged in fostering on their own without an animal shelter or rescue program. One-third of the total sample, and more than two-thirds of participants who had already fostered cats and kittens on their own, were interested in fostering in partnership with an animal shelter. More than 50% of individuals who were interested in fostering had not seen advertising for fostering programs; Spanish-language participants were significantly less likely than expected to have encountered program advertisements. The most prevalent concerns about fostering in our sample were centered on the time (79%), cost (78%), and space (77%) required to engage in fostering. Text, email, social media, and mail were among the most preferred methods for marketing and communication, with some variation between Spanish and English language respondents. Opportunities for increasing engagement included leveraging these communication methods, improving the promotion of program advertisements using animal-welfare and cost-focused messaging approaches, and improving the dissemination and marketing of Spanish-language materials. Providing community members with realistic expectations of the time, resources, and support they will get from animal welfare organizations may improve engagement in KFPs, as well as identifying alternative resources and supports (e.g., transportation, in-home veterinary visits) to assist community members in serving animals in their community.